Analisis Prokrastinasi Dalam Mengerjakan Skripsi Pada Mahasiswa Jurusan Pendidikan Ekonomi Angkatan 2015 Universitas Negeri Padang - Fitrah Fitrah; Agus Irianto (Jurnal Ecogen, 2019)
This Research aims to identify and analyze the influence of adversity quotient and parents' socio-economic conditions on procrastination in doing thesis on students of 2015 economic education majoring in Padang State University. The population in this research were students of 2015 economic education majoring in Padang State University who were taking a thesis course. The analytical method used is multiple regression analysis and data analysis process using the SPSS version 21 program. The results show that 1) there is a significant influence between adversity quotient and parents' socio-economic conditions on procrastination in working on a thesis. 2) there is a significant negative effect between adversity quotient on procrastination in working on a thesis. 3) there is a significant negative effect between parents' socio-economic conditions on procrastination in working on a thesis.Keyword: adversity quotient, socio-economic, procrastination